Vanadyl sulphate ameliorates biomarkers of endothelial injury and coagulation and thrombosis in a rat model of hyperglycaemia. (4th March 2022) - Haidara, Mohamed A.; Al-Ani, Bahjat; Bin-Jaliah, Ismaeel; Shams Eldeen, Asmaa M.; Morsy, M. D.
Abstract: Background: We sought to determine whether the insulin mimicking agent, vanadyl sulphate (Van) can inhibit biomarkers of endothelial injury and coagulation and thrombosis induced by a moderate level of hyperglycaemia. Material and methods: Hyperglycaemia was induced in rats by a single injection of streptozotocin (STZ, 50 mg/kg) two weeks after being fed on a high-fat diet (model group). The treatment group started Van (20 mg/kg/day) treatment one-week post STZ injection and continued on Van until being sacrificed at week 10. Results: Administration of Van to the model group significantly ( p < .05) ameliorated dyslipidemia and biomarkers of inflammation (TNF-α, IL-6, and hsCRP) and endothelial injury (E-selectin, P-selectin, sICAM-1, sVCAM-1, and ET-1). Van also significantly inhibited hyperglycaemia-induced blood levels of coagulation (vWF) and thrombosis (PAI-1 and fibrinogen) biomarkers. Conclusions: Vanadyl sulphate effectively suppresses hyperglycaemia-induced endothelial injury, coagulation and thrombosis, which is associated with the inhibition of inflammation and dyslipidemia.